Interactive influence of basalt fibres and pozzolanic additives on the mechanical and microstructural properties of self-compacting concrete - Olive Sharon R P; SenthilPandian M (Case Studies in Construction Materials)
This paper investigates the influence of adding Basalt Fibres (BF) on the workability, mechanical properties, and microstructural characteristics of Self-Compacting Concrete (SCC) incorporating Fly Ash (FA) and Silica Fume (SF) as pozzolanic additives. Initially, three modified mixes (SCC1, SCC2, SCC3) are prepared by partially replacing cement with a constant FA content of 25 % and varying SF content from 5 % to 15 % with an increment of 5 % and the optimal mix is identified based on the improved rheological and hardened properties. To enhance the properties of the selected SCC mix further, the BFs are incorporated at varying percentages (0.1–0.3 %) by volume of concrete and examined. The microstructural properties are analysed using Scanning Election Microscope (SEM) with Energy-dispersive X-ray (EDX) analysis and X-ray Diffraction (XRD) spectroscopy. Further, the Response Surface Methodology (RSM) is used to examine the intricate interaction between SF (5–15 %) and BF (0.1–0.3 %), statistically validate models, and optimise SF and BF contents. The results depict that SF content beyond 10 % negatively impacts the workability and strength of SCC. Thus, SCC2 (25 % FA and 10 % SF) is identified as an optimal mix based on the improved rheological and mechanical properties. Adding BF, particularly at 0.2 %, further enhanced the mechanical properties without compromising the workability. Compared to conventional SCC, the compressive strength rises by 20.38 % at 56 days, and the split tensile strength and ultrasonic pulse velocity (UPV) improve by 24.66 % and 27.25 % at 28 days, respectively. The SEM and XRD analysis of the optimized SCC mix reveals improved microstructural properties, showing a densified matrix with better fibre-matrix interaction and the formation of secondary C-S-H products. RSM validated all the experimental results with a mean error of less than 4 %, confirming the reliability of the findings. This research demonstrates that using FA and SF as partial cement replacements and BF reinforcement can develop high-performance, sustainable SCC suitable for advanced construction applications.